2018
DOI: 10.1002/app.46455
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of α‐ZrP and graphene oxide nanofillers on the gas barrier properties of PVA films

Abstract: Two types of 2D nanofillers, α‐zirconium phosphate (α‐ZrP) and graphene oxide (GO), were synthesized and incorporated into poly(vinyl alcohol) (PVA) with 1 wt % loading level at various α‐ZrP:GO (Z:G = 5:1, 2:1, 1:1, 1:2, and 1:5) ratios. The resulting nanocomposites were tested for barrier properties by casting films from solution. The structure and morphology of α‐ZrP and GO were characterized by Fourier‐transform infrared spectroscopy, atomic force microscope, scanning electron microscopy, transmission elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…From Figure , it can be deduced that the π‐π stacking interactions between GP‐Cl nanosheets prevent PVA chains from slipping, which greatly enhances the tensile strength of the hybrid film . (e) Crystallinity of PVA . The crystallinity of PVA was apparently increased with GP‐Cl owing to the “molecule movement restriction” effect (as shown in Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…From Figure , it can be deduced that the π‐π stacking interactions between GP‐Cl nanosheets prevent PVA chains from slipping, which greatly enhances the tensile strength of the hybrid film . (e) Crystallinity of PVA . The crystallinity of PVA was apparently increased with GP‐Cl owing to the “molecule movement restriction” effect (as shown in Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The extremely great mechanical properties of graphene‐based material could enable it to be a potential reinforcement material . (g) Dispersion of GP‐Cl nanosheets in PVA matrices . GP‐Cl had a stronger effect on mechanical strength when it was well dispersed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The synergy of multiple nanofillers especially among those with different dimensions can bring about benefits similar to that of functionalization, including enhancing nanofiller dispersion, promoting adhesion with polymer matrix and improving gas selectiveness [164,[261][262][263]. Wong et al [81] and Zhang et al [264] demonstrated that hybridizing CNT with GO could improve the overall stability of the suspension in aqueous solution.…”
Section: Nanofiller Hybridizationmentioning
confidence: 99%